Habilitación y obsolescencia de marcadores discursivos - Ridruejo, Emilio (Studia Romanica Posnaniensia, 2019)
The starting hypothesis of the article is that the discursive operators of Spanish have not been enabled by grammaticalization processes identical to those of other grammatical components (such as verbal or nominal morphemes or prepositions and conjunctions), since there has been no reduction in the functional scope nor a total bleaching, so that its link with the original lexical items has not disappeared. The consequence is that markers are not integrated into paradigms as closed as grammatical paradigms and both their obsolescence and their renewal, therefore, follow similar patterns to what happens in the evolution of the lexicon. This hypothesis is tried to verify in the article by means of the examination of some discursive markers that, having been used diachronically in Spanish, have been abandoned in a relatively short time.